Review article: linaclotide for the management of irritable bowel syndrome with constipation. Issue 4 (16th January 2014) - Layer, P.; Stanghellini, V.
Summary Background Irritable bowel syndrome with constipation (IBS‐C) represents a significant burden to patients and healthcare systems due to its prevalence and lack of successful symptomatic resolution with established treatment options. Linaclotide 290 μg has recently been approved by the European Medicines Agency (EMA) for moderate‐to‐severe IBS‐C and by the US Food and Drug Administration for IBS‐C (290 μg dose) and for chronic constipation (145 μg dose). Aim To summarise data leading to the approval of linaclotide for IBS‐C, with focus on EMA‐pre‐specified outcome measures. Methods Literature search of a peer‐review database (PubMed) and review of congress abstracts on linaclotide preclinical and clinical trial data in IBS‐C. Results Preclinical studies suggest that the guanylate cyclase C agonist (GCCA) linaclotide acts through elevation of cyclic guanosine monophosphate (cGMP) levels, leading to accelerated gastrointestinal (GI) transit through increased fluid secretion and reduced visceral hypersensitivity. Clinical trial data demonstrate that linaclotide improves abdominal symptoms (pain, bloating) and bowel symptoms (constipation) compared with placebo in patients with IBS‐C. The most frequent side effect, diarrhoea, results from the therapeutic action of linaclotide. Linaclotide acts locally in the GI tract with minimal systemic exposure, resulting in low oral bioavailability and thus a low risk of relevant systemic adverse effects. Conclusion Linaclotide, a first‐in‐class GCCA, is a promising new drug with a novel, dual mechanism of action that, unlike more well‐established agents, can relieve the abdominal pain, bloating and constipation associated with IBS‐C and has a low propensity for systemic side effects.